Identification of genetic variants for clinical management of familial colorectal tumors - Mev Dominguez-Valentin; Sigve Nakken; Hélène Tubeuf; Daniel Vodak; Per Olaf Ekstrøm; Anke M. Nissen; Monika Morak; Elke Holinski-Feder; Alexandra Martins; Pål Møller; Eivind Hovig (BMC Medical Genetics, 2018)
Abstract Background The genetic mechanisms for families who meet the clinical criteria for Lynch syndrome (LS) but do not carry pathogenic variants in the mismatch repair (MMR) genes are still undetermined. We aimed to study the potential contribution of genes other than MMR genes to the biological and clinical characteristics of Norwegian families fulfilling Amsterdam (AMS) criteria or revised Bethesda guidelines. Methods The Hereditary Cancer Biobank of the Norwegian Radium Hospital was interrogated to identify individuals with a high risk of developing colorectal cancer (CRC) for whom no pathogenic variants in MMR genes had been found in routine diagnostic DNA sequencing. Forty-four cancer susceptibility genes were selected and analyzed by using our in-house designed TruSeq amplicon-based assay for targeted sequencing. RNA splicing- and protein-dedicated in silico analyses were performed for all variants of unknown significance (VUS). Variants predicted as likely to affect splicing were experimentally analyzed by resorting to minigene assays. Results We identified a patient who met the revised Bethesda guidelines and carried a likely pathogenic variant in CHEK2 (c.470 T > C, p.I157T). In addition, 25 unique VUS were identified in 18 individuals, of which 2 exonic variants (MAP3K1 c.764A > G and NOTCH3 c.5854G >A) were analyzed in the minigene splicing assay and found not to have an effect on RNA splicing. Conclusions Among high-risk CRC patients that fulfill the AMS criteria or revised Bethesda guidelines, targeted gene sequencing identified likely pathogenic variant and VUS in other genes than the MMR genes (CHEK2, NOTCH3 and MAP3K1). Our study suggests that the analysis of genes currently excluded from routine molecular diagnostic screens may confer cancer susceptibility.